2018
DOI: 10.1108/mi-05-2017-0022
|View full text |Cite
|
Sign up to set email alerts
|

Development of a current mirror-integrated pressure sensor using CMOS-MEMS cofabrication techniques

Abstract: Purpose This paper aims to describe the fabrication and characterization of current mirror-integrated microelectromechanical systems (MEMS)-based pressure sensor. Design/methodology/approach The integrated pressure-sensing structure consists of three identical 100-µm long and 500-µm wide n-channel MOSFETs connected in a resistive loaded current mirror configuration. The input transistor of the mirror acts as a constant current source MOSFET and the output transistors are the stress sensing MOSFETs embedded n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…Table 2 gives the various piezoresistive coefficients of p-and n-MOSFETs and it is observed that each of the π-coefficients of NMOS is having different magnitude with opposite sign as compared with that of PMOS. From literature [35][36], it has been found that the sign of overall piezoresistive coefficient (π) is negative for PMOS and positive for NMOS. Therefore, the effect of similar stress on the channel resistance and carrier mobility of pressure sensing NMOS and PMOS transistors will be opposite in nature, which is governed by Equation (5).…”
Section: Electrical Transduction Mechanism: Piezo-resistive Effect In...mentioning
confidence: 99%
See 1 more Smart Citation
“…Table 2 gives the various piezoresistive coefficients of p-and n-MOSFETs and it is observed that each of the π-coefficients of NMOS is having different magnitude with opposite sign as compared with that of PMOS. From literature [35][36], it has been found that the sign of overall piezoresistive coefficient (π) is negative for PMOS and positive for NMOS. Therefore, the effect of similar stress on the channel resistance and carrier mobility of pressure sensing NMOS and PMOS transistors will be opposite in nature, which is governed by Equation (5).…”
Section: Electrical Transduction Mechanism: Piezo-resistive Effect In...mentioning
confidence: 99%
“…In another approach, piezo-MOS sensing, that is piezoresistive effect in MOSFET, has also found a promising application in the monolithic integration of CMOS and MEMS [19][20][21]. Piezo-MOSFETs integrated with microstructures have attracted significant interest among the researchers all over the world [22][23][24][25][26][27][28][29][30][31][32][33][34][35][36]. In particular, various types of MOSFET based pressure transducers have been studied, designed and developed.…”
Section: Introductionmentioning
confidence: 99%
“…Under externally applied pressure, carrier mobility of transistors M2 and M3 changes due to the piezoresistive effect in MOSFETs (Bradley et al, 2001). The variation in carrier mobility of pressure-sensing MOSFETs M2 and M3 results in the variation of their drain currents and voltages (Rathore et al, 2015;Kumar et al, 2018). An output voltage V out corresponding to the input applied pressure is obtained across the drain terminals of pressure-sensing MOSFETs M2 and M3 as shown in Figure 1 and is given by the following equation:…”
Section: Proposed Pressure Transducer Design and Workingmentioning
confidence: 99%
“…In our earlier work, design, modeling and simulation of n-and p-channel MOSFET-based current mirror-integrated pressure transducer with lesser dimension had been designed and simulated (Kumar et al, 2016). However, the fabrication and testing results of n-channel MOSFET-based current mirrorintegrated pressure transducer had been presented (Kumar et al, 2018). In this work, a resistive loaded p-channel MOSFETbased current mirror-integrated pressure transducer has been fabricated, tested and compared with our earlier reported work.…”
Section: Introductionmentioning
confidence: 95%
“…Widespread applications of Microelectromechanical systems (MEMS) as sensors (Amiri and Kordrostami, 2018;Hwang et al, 2019;Kumar et al, 2018;Rafiee et al, 2016), switches (Samaali et al, 2015;Kim et al, 2018) and energy harvesters (Kordrostami and Roohizadegan, 2019;Kordrostami and Roohizadegan, 2018;Ghoddus et al, 2019;Ghoddus and Kordrostami, 2018) have revolutionized the technology in terms of the size of the devices (particularly the sensors) and high integration capability with electric circuits (Rafiee et al, 2017;Amiri et al, 2020). Micromachined pressure sensor is the most commonly used MEMS sensors.…”
Section: Introductionmentioning
confidence: 99%